Karakteristik Dan Perilaku Wisatawan Asing Di Era Digital Yang Menggunakan Instagram Sebagai Travel Guide Di Kawasan Canggu, Bali - Putu Dia Cahya Ratih; I Gusti Agung Oka Mahagangga; I Made Bayu Ariwangsa (JURNAL DESTINASI PARIWISATA, 2021)
Nowadays, the use of social media instagram as a media for tourism information and travel guide by tourists increase rapidly. Especially in Canggu area Bali, which is one of top 5 popular destination in Bali based on the number of top keywords on instagram. The aim of this research is to identify and link the charactheristics and behavior of foreign tourists in digital era who use instagram as a travel guide in Canggu area, Bali. This research used quantitative methods and used simple descriptive statistic analysis. The result of this research shows that the charactheristics and behavior of foreign tourist in Canggu area, Bali are related each others. Data showed that dominance of the charactheristics from young tourists, with an average educational background of bachelor degree, and work as a blogger can influences of tourists’ behavior in social media. They have multy creativity to shared their tourist experiences to public. Keywords: Instagram as Travel Guide, Tourist Charactheristics, Tourist Behavior, Canggu